Lending Growth Determinant on Rural Banks in Denpasar - Ni Wayan Sulistiyani; Agus Wahyudi Salasa Gama; Ni Putu Yeni Astiti (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2019)
This study aims to examine the determinant of lending growth on rural bank in Denpasar. the determinant of lending growth consists of Third-Party Funds, Capital Adequacy Ratio, NonPerforming Loans, Loan to Deposit Ratio, and Return on Assets. In this study there were 18 rural banks being sampled this research was conducted in three years of observation, from 2016 to 2017. Data analysis techniques used in this study are multiple linear regression. The results of the study show that Third Party Funds and Loan to Deposit Ratio can affect lending growth positively and significantly. while the Capital Adequacy Ratio, Non-performing Loans, and Return on Assets are not able to influence lending growth in rural banks in Denpasar. Keywords: Lending Growth, Rural Banks, Capital Adequacy, Non-Performing Loan